Incidence of early diaphragmatic dysfunction after lung transplantation: results of a prospective observational study. Issue 9 (8th July 2021) - Crothers, Elise; Kennedy, David S.; Emmanuel, Sam; Molan, Nikki; Scott, Sean; Rogers, Kris; Glanville, Allan R.; Ntoumenopoulos, George
Abstract: Background: Diaphragmatic dysfunction is common after cardiothoracic surgery, but few studies report its incidence and consequences after lung transplantation. We aimed to estimate the incidence of diaphragmatic dysfunction using ultrasound in lung transplant patients up to 3 months postoperatively and evaluated the impact on clinical outcomes. Methods: This was a single‐center prospective observational cohort study of 27 lung transplant recipients using diaphragmatic ultrasound preoperatively, at 1 day, 1 week, 1 month, and 3 months postoperatively. Diaphragmatic dysfunction was defined as excursion < 10 mm in men and < 9 mm in women during quiet breathing. Clinical outcomes measured included duration of mechanical ventilation, length of stay (LOS) in Intensive Care (ICU), and hospital LOS. Results: Sixty‐two percentage of recipients experienced new, postoperative diaphragmatic dysfunction, but the prevalence fell to 22% at 3 months. No differences in clinical outcomes were found between those with diaphragmatic dysfunction compared to those without. Patients who experienced diaphragmatic dysfunction at 1 day postoperatively were younger and had a lower BMI than those who did not. Conclusions: Diaphragmatic dysfunction is common after lung transplant, improves significantly within 3 months, and did not impact negatively on duration of mechanical ventilation, LOS in ICU or hospital, or discharge destination.